The Relationship Between Demographic Features and Iranian EFL Teachers’ Attachment Style - Mansoor Ganji; Farzane Safarzade Samani (Profile: Issues in Teachers' Professional Development)
This study investigated Iranian English as a foreign language teachers’ attachment styles and possible influential factors such as age, teaching experience, gender, and educational degree. The participants were 108 female and 79 male Iranian English teachers, chosen through convenience and snowball sampling. Using Google forms, a researcher-made questionnaire was sent to the participants. There was a positive relationship between age and a secure style, and a negative relationship between fearful and preoccupied styles and age. Further, there was a positive correlation between a secure style and teaching experience, and a negative relationship between fearful and preoccupied styles and teaching experience. Male teachers were more secure, and educational degree made no difference in secure and preoccupied styles.